Antigen-Presenting Cells and T Cells Interact in a Specific Area of the Intestinal Mucosa Defined by the Ccl25-Ccr9 Axis in Medaka - Aghaallaei, Narges; Agarwal, Rashi; Benjaminsen, Joergen; Lust, Katharina; Bajoghli, Baubak; Wittbrodt, Joachim; Feijoo, Carmen G. (Frontiers in Immunology, 2022)
Organized intestinal mucosal immune response appears to be restricted to tetrapods. In teleost fish, there is no evidence for the existence of a particular region that facilitates the interaction of antigen-presenting cells (APCs) and T cells, such as secondary lymphoid organs. Indeed, despite their importance in the defense against pathogens, the location and manner of APC-T cell interaction within the fish gut is unknown. Here, using non-invasive live imaging of newly developed transgenic reporter lines, we addressed the spatial organization and behavior of APCs and T cells in the intestine of medaka fish both during homeostasis and inflammation. We report that Ccr9a+ T cells are recruited to a band in the lamina propria next to the muscularis mucosa in which Ccl25-expressing mesenchymal cells are present. Ccr9a+ T cells contact APCs for several minutes, in a process mediated by connexin 43. This type of interaction was observed in homeostasis and inflammation, with the interaction being longer and more frequent during inflammation. Thus, our results demonstrate that the mucosal immune response in the intestine of fish is organized and endowed with a specific region with specialized microenvironment and function.